II. Meşrutiyet Dönemi'inde Serbesti Gazetesi ve başyazarı Hasan Fehmi'nin misyonu - Demir, Hasan Fehmi (My University, 2018)
Hasan Fehmi’nin ölümü ile beraber, İttihat ve Terakki’ye karşı olan muhalefet giderek artmış, özellikle çoğunluğunu öğrencilerin oluşturduğu kitleler, hükümet üzerinde baskı oluşturarak bu cinayetin aydınlatılmasını istemiştir. Muhalif basın tek bir ağız olarak Hasan Fehmi Bey’i ‘’Şehid-i Hürriyet’’ ilan etmiştir.

İttihat ve Terakki Community which is the secret society, took over the government step by step with second constitutionalist period in Ottoman Empire, causes many political assassinations. Serbesti newspaper’s main publication policy is based on advocating decentralism in place of the centrical administration of the Unionists. However, supporting of Prince Sabahattin's Ahrar Party have caused the newspaper to be targeted by the Unionists
Keywords: Asassination of Hasan Fehmi; Assassinations; Basın; Gazeteciler; Hasan Fehmi Bey, 1874-1909; Hasan Fehmi suikastı; History; Journalists; Political and social views; Political crimes and offenses; Political policy; Politics and government; Press; serbesti hasan fehmi serbesti hasan fehmi; Serrbesti gazetesi; Serrbesti newspaper; Siyasal suçlar ve suçlular; Siyaset ve yönetim; Siyasi politikası; Siyasi ve sosyal görüşleri; Suikastler; Tarih; Turkey; Türkiye